The seventeenth annual Rocky Mountain reproductive sciences symposium: scientific proceedings - Twiggs, Jasmin A., author; Hansen, Thomas R., author; Winger, Quinton A., author (Colorado State University. Libraries, 2025)
The Rocky Mountain Reproductive Science Symposium (RMRSS) is a one-day public conference held annually since 2008. Developed and hosted by the Animal Reproduction and Biotechnology Laboratory at Colorado State University, the symposium was established to foster regional collaboration and serve as a forum for the exchange of ideas between the animal agricultural (USDA-NIFA) and human biomedical (NIH) research communities. RMRSS provides a platform for students, trainees, faculty, and professionals to share expertise, generate new scientific ideas, and expand access to shared resources. Its mission is to promote student training, enhance communication, and support collaborative research across diverse reproductive science models. While the event primarily draws regional participants, it also welcomes attendees from across the country each spring. The 17th annual Rocky Mountain Reproductive Sciences Symposium, held on May 9, 2025, received a record number of 62 abstract submissions and welcomed over 160 participants. Centered on the theme Ovarian Aging and Pathophysiology, the program featured two keynote presentations, eight trainee platform talks, five elevator pitch talks, and two poster sessions showcasing diverse research across reproductive science disciplines. The clinical science keynote address was delivered by Dr. Nanette Santoro (University of Colorado Anschutz School of Medicine), titled "Understanding the Physiology of Ovarian Aging." The basic science keynote was presented by Dr. John S. Davis (University of Nebraska Medical Center), titled "Ovarian Hippo/YAP1 Signaling Across the Reproductive Health Span." The 2025 RMRSS was made possible through generous support from the U.S. Department of Agriculture National Institute of Food and Agriculture (NIFA) via the Agriculture and Food Research Initiative (AFRI) and Animal Reproduction Program (award number 2024-67015-43034), the Society for the Study of Reproduction, the Animal Reproduction and Biotechnology Laboratory, and the Department of Biomedical Sciences.
Hosted by Animal Reproduction and Biotechnology Laboratory, Colorado State University.
Includes program information, schedule and abstracts only.
Keywords: conference; reproductive science; symposia; congress